Treating tropical grass with fibrolytic enzymes from the fungus Trichoderma reesei: Effects on animal performance, digestibility and enteric methane emissions of growing lambs - Sakita, Gabriel Zanuto; Lima, Paulo de Mello Tavares; Abdalla Filho, Adibe Luiz; Bompadre, Thiago Francisco Ventoso; Ovani, Vagner S.; Chaves, Camila de Miranda e Silva; Bizzuti, Beatriz Elisa; Costa, Wilian dos Santos da; Paim, Tiago do Prado; Campioni, Tania Sila [UNESP]; Oliva Neto, Pedro de [UNESP]; Bremer-Neto, Hermann; et al. (Elsevier, 2022)
Food security and climate change concerns are pressing livestock production industry to seek sustainable practices to increase productivity while reducing the intensity of enteric methane (CH4) emissions. In this scenario, the use of enzyme products in ruminant nutrition may be an important alternative to meet future increased demands for animal products with reduced environmental impacts. The objective of this study was to evaluate the effects of treating forage with a fibrolytic enzymes extract (FEE), produced by Trichoderma reesei, on animal performance, blood biochemical parameters, nutrient digestibility, ruminal fermentation, and enteric CH4 production of growing lambs. Nineteen Santa Inês growing lambs were divided into two groups: control (CTL) and enzyme (ENZ). The animals were fed with 700 g/kg of tifton-85 hay and 300 g/kg (as fed basis) of concentrate mixture for 73 days. The FEE was manually applied 24 h before each feed supply. Initially, animals were kept in individual pens for the growth performance trial (15 days of adaptation plus 45 for data collection), then were taken to metabolic cages (seven days) and to gas measurement chambers (six days) for the metabolism assay and determination of CH4 production, respectively. No effects (P > 0.05) were observed on dry matter intake (DMI), average daily gain (ADG), and feed conversion ratio. However, ENZ animals showed higher proportion of body weight gain (PBWG) when considering the entire growth performance period (P < 0.05). Analysis of blood parameters indicated that FEE did not impair animals’ health. Lambs fed forages treated with FEE showed 12% higher acid detergent fiber (ADF) digestibility (P < 0.05) and 20% lower enteric CH4 yield (i.e. per kg of digestible organic matter intake) (P < 0.05). Microbial protein synthesis, pH, ammonia nitrogen, short-chain fatty acids concentration and protozoa population were not affected by the addition of FEE (P > 0.05). The results indicated that FEE can be used in diets of lambs, leading to higher PBWG, improving ADF digestibility and reducing CH4 yield, suggesting its potential suitability as a strategy to increase animal productivity and contribute to the mitigation of enteric CH4 production, especially when animals are fed poor-quality forages.
Keywords: Cellulase; CH4 mitigation; Growth performance; Ruminant; Sustainability; Xylanase